2018
DOI: 10.1016/j.simyco.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Cladosporium species in indoor environments

Abstract: As part of a worldwide survey of the indoor mycobiota about 520 new Cladosporium isolates from indoor environments mainly collected in China, Europe, New Zealand, North America and South Africa were investigated by using a polyphasic approach to determine their species identity. All Cladosporium species occurring in indoor environments are fully described and illustrated. Fourty-six Cladosporium species are treated of which 16 species are introduced as new. A key for the most common Cladosporium species isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
146
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(152 citation statements)
references
References 49 publications
(193 reference statements)
6
146
0
Order By: Relevance
“…In addition, Acremonium, Cladosporium and Sarocladium were previously reported in cereals (maize and rice) and cocoa powder beverages in Nigeria (Makun et al, 2011;Egbuta et al, 2015). Cladosporium has also been reported in fruits from Nigeria, chili and Musa species (banana and plantains) from different countries (Bensch et al, 2018). Acremonium and Sarocladium are two phenotypically-related genera and a comprehensive phylogenetic study led to the re-allocation of some hypocrealean Acremonium (including the clinically important species A. strictum) to Sarocladium (Summerbell et al, 2011;Giraldo et al, 2015).…”
Section: Fungal Occurrence (Load and Incidence) In Dried Rte Foods Anmentioning
confidence: 99%
“…In addition, Acremonium, Cladosporium and Sarocladium were previously reported in cereals (maize and rice) and cocoa powder beverages in Nigeria (Makun et al, 2011;Egbuta et al, 2015). Cladosporium has also been reported in fruits from Nigeria, chili and Musa species (banana and plantains) from different countries (Bensch et al, 2018). Acremonium and Sarocladium are two phenotypically-related genera and a comprehensive phylogenetic study led to the re-allocation of some hypocrealean Acremonium (including the clinically important species A. strictum) to Sarocladium (Summerbell et al, 2011;Giraldo et al, 2015).…”
Section: Fungal Occurrence (Load and Incidence) In Dried Rte Foods Anmentioning
confidence: 99%
“…Cladosporium halotolerans which was isolated from both washing machines is a hygrophil fungi isolated from various environments such as bathrooms and oceans, and were listed as a new species in 2007Zalar et al, 2007 . Although C. cladosporioides and C. sphaerospermum were known as the main species of the Cladosporium genus Samson et al, 2004 , with the recent prevalence of genetic analysis, it has become recognized that C. halotolerans is the main Cladosporium in household environments Sandoval-Denis et al, 2015;Bensch et al, 2018 . In indoor environments in Japan, C. halotolerans is also a more dominant Cladosporium than C. sphaerospermum, and the fact C. cladosporioides sensu stricto barely exists in Japanese household environments, is gaining recognition Kobayashi et al, 2012 . As the 3 strains we have analyzed in this study are C. halotolerans, it can be estimated that there is a similar tendency also in washing machines.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, Cladosporium is one of the major fungi in household environments Samson et al, 2004 , however, in a research conducted in Osaka, it was suggested that Cladosporium was not predominant in washing machines Hamada, 2002a;2004 . From fungal flora research the authors have conducted in households in Saitama and Tokyo, the dominant species in airborne fungi and house dust are overwhelmingly Aspergillus and Cladosporium Hashimoto and Kawakami, 2015;2018;Kawakami et al, 2016 . However, in the washing machines in this study, the number of isolated Cladosporium was low compared to washing machines or bathrooms, as Scolecobasidium humicola from genetic analysis. In their study, they used strain NBRC 32054 S. humicola , as a reference.…”
Section: Discussionmentioning
confidence: 99%
“…Cladosporium was also found in commercial black coffee powder samples in Malaysia, although in a lower frequency than Fusarium (Rahim et al, 2011). Cladosporium is known as the most abundant fungi in outdoor and indoor air (Bensch et al, 2018). The conidium Cladosporium is adaptable in the air because it is small, dry, lightweight, and resistant to sunlight (Pitt and Hocking, 2009).…”
Section: Mold Isolates From Coffee Before Brewingmentioning
confidence: 99%